Penerimaan Masyarakat Terhadap Modernisasi Pembangunan Stadion Sepak Bola di Kabupaten Kotabaru - Hamid, Ismar; Irsan, Irsan; Hidayat, Rahmat; Yusril, Yusril; Nugroho, Arif Rahman; Fauzan, Lazuardy Akbar; Pratama, Muhammad Daffa (Mahesa Research Center, 2025)
Modernization of development has become the development goal of the Kotabaru district government through the construction of a modern football stadium. This article aims to explore and analyze the potential social, economic, and public acceptance impacts of constructing a football stadium in Kotabaru Regency. To address this problem, a literature analysis and field data were employed. The data were collected through observation and in-depth interviews and analyzed qualitatively. This study concludes that the presence of a football stadium in the new city district has a social impact as a public space. The economic impact is the creation of formal and informal sector jobs, driving economic growth and local revenue. The construction of a football stadium has the potential to generate conflict, particularly regarding land acquisition, unequal distribution of economic benefits, and conflict between football fans. Active community participation as a form of positive acceptance in both the planning and management processes can reduce the potential for conflict, strengthen transparency, and increase social legitimacy for the construction of a football stadium.